Electrochemical Determination of Manganese Solubility in Mercury via Amalgamation and Stripping in the Room Temperature Ionic Liquid n-Hexyltriethylammonium Bis(trifluoromethanesulfonyl)imide, [N-6,N-2,N-2,N-2][NTf2] - Rogers, E; Sljukic, B; Hardacre, C; Compton, R (2008)
The solubility of manganese in mercury was determined electrochemically via amalgamation and stripping in the room temperature ionic liquid n-hexyltriethylammonium bis(trifluoromethanesulfonyl)imide, [N 6,2,2,2][NTf2]. A hemispherical mercury electrode was made by electrodepositing mercury onto a planar platinum microelectrode. Cyclic voltammetry of Mn2+ in [N6,2,2,2][NTf2] at the mercury microhemisphere electrode was investigated at temperatures of 298, 303 and 313 K. The solubility of Mn in Hg was determined on the basis of the charge under the reduction peak (Mn2+ → Mn0) and the corresponding reoxidation. © 2008 WILEY-VCH Verlag.